2003
DOI: 10.1124/dmd.31.4.392
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide-Mediated Modulation of Cytochromes P450 in Stat1 Null Mice

Abstract: ABSTRACT:Signal transducer and activator of transcription (Stat), a family of transcriptional factors, has been demonstrated to play a critical role in gene regulation in response to inflammatory cytokines, such as interferon and interleukin-6. Inflammatory cytokines and bacterial endotoxin are known to suppress, in most of cases, the constitutive or induced cytochromes P450 (P450) in animals and humans. However, it is not clear if the suppression of P450 by cytokines is through the Stat-signaling pathway. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…For example, an initial study suggested that LPS-mediated alteration of hepatic and renal P450 expression was mediated by peroxisome proliferator-activated receptor-␣ (Barclay et al, 1999). However, subsequent experiments have demonstrated that LPS-mediated downregulation of hepatic P450 expression is independent of peroxisome proliferator-activated receptor-␣, pregnane X receptor, and signal transducer and activator of transcription-1 (Pan et al, 2003;Richardson and Morgan, 2005). Although we did not directly investigate the mechanism by which LPS alters P450 expression and metabolic activity, the observed isoform-and tissue-specific response suggests that the mechanism is complex and most likely involves multiple transcription factors that vary across isoforms and tissues.…”
Section: Downloaded Frommentioning
confidence: 77%
“…For example, an initial study suggested that LPS-mediated alteration of hepatic and renal P450 expression was mediated by peroxisome proliferator-activated receptor-␣ (Barclay et al, 1999). However, subsequent experiments have demonstrated that LPS-mediated downregulation of hepatic P450 expression is independent of peroxisome proliferator-activated receptor-␣, pregnane X receptor, and signal transducer and activator of transcription-1 (Pan et al, 2003;Richardson and Morgan, 2005). Although we did not directly investigate the mechanism by which LPS alters P450 expression and metabolic activity, the observed isoform-and tissue-specific response suggests that the mechanism is complex and most likely involves multiple transcription factors that vary across isoforms and tissues.…”
Section: Downloaded Frommentioning
confidence: 77%
“…On the other hand, numerous studies indicated that inflammation and infection reduce hepatic CYP levels in various species including human, rat and mouse (Morgan, 1997(Morgan, , 2001. The effect of LPS on P450 expression is very well documented in a variety of systems and tissues (Renton and Nicholson, 2000;Li-Masters and Morgan, 2001;Morgan et al, 2002;Pan et al, 2003;Kalitsky-Szirtes et al, 2004). LPS-induced downregulation of cyp3a in liver has also been demonstrated in mouse model (Sewer et al, 1998).…”
Section: Introductionmentioning
confidence: 92%
“…As was expected, BCG lost its ability to phosphorylate both STAT1 and STAT3 in IL-6 KO mouse livers. Pan et al (2003) reported that CYP3A11 and 2C29 mRNAs are markedly down-regulated by LPS in STAT1 KO mice and in wild-type mice. Thus, STAT1 is unlikely to be involved in LPS-induced CYP3A11 and 2C29 mRNA down-regulation.…”
Section: Figurementioning
confidence: 99%